2022
DOI: 10.1038/s41368-021-00152-2
|View full text |Cite
|
Sign up to set email alerts
|

Dental stem cell-derived extracellular vesicles as promising therapeutic agents in the treatment of diseases

Abstract: Dental stem cells (DSCs), an important source of mesenchymal stem cells (MSCs), can be easily obtained by minimally invasive procedures and have been used for the treatment of various diseases. Classic paradigm attributed the mechanism of their therapeutic action to direct cell differentiation after targeted migration, while contemporary insights into indirect paracrine effect opened new avenues for the mystery of their actual low engraftment and differentiation ability in vivo. As critical paracrine effectors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“… 32 34 Recently, EVs have gained more attention as a protection or repair mechanism against pulp infection, and it was found that EV derived from LPS-stimulating dental cells protect cells from apoptosis and promote the proliferation, migration, and differentiation of several dental stem cells, 12 15 however, our data here found that EV derived from LPS-stimulated DPCs suppressed odontoblastic differentiation of SCAPs, which suggests a pathological role of EV in AP progression. The paradoxical roles of LPS-stimulated EV can be attributed to the heterogeneity among different subtypes of dental cells-derived EVs, 35 meanwhile, given the variation of LPS concentration and precondition time duration between each study, another explanation is that a different role of LPS-stimulated EVs may be associated with the severity of infection.…”
Section: Discussionmentioning
confidence: 99%
“… 32 34 Recently, EVs have gained more attention as a protection or repair mechanism against pulp infection, and it was found that EV derived from LPS-stimulating dental cells protect cells from apoptosis and promote the proliferation, migration, and differentiation of several dental stem cells, 12 15 however, our data here found that EV derived from LPS-stimulated DPCs suppressed odontoblastic differentiation of SCAPs, which suggests a pathological role of EV in AP progression. The paradoxical roles of LPS-stimulated EV can be attributed to the heterogeneity among different subtypes of dental cells-derived EVs, 35 meanwhile, given the variation of LPS concentration and precondition time duration between each study, another explanation is that a different role of LPS-stimulated EVs may be associated with the severity of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the transfer of RNA through EVs secreted by SC-like differentiated adipose stem cells has been shown to promote neurite outgrowth ( Ching et al, 2018 ). The proliferation and maintenance of human dental pulp cells have also been shown to be promoted by SDEVs ( Li et al, 2022 ).…”
Section: Various Kinds Of Extracellular Vesicles In Glia-neuron Intra...mentioning
confidence: 99%
“…Therefore, DPSC-sEV may be acquired more conveniently with higher production and bioactivities than BMSC-sEV. DPSC-sEV have also been documented to exert therapeutic effects on skin wounds, spinal cord injury, and mandible and calvarial bone defects [ 18 , [21] , [22] , [23] , [24] ]. However, it is largely unknown whether DPSC-sEV can simultaneously directly suppress the macrophage inflammatory response and osteoclastogenesis to induce bone repair in inflammatory osteolysis.…”
Section: Introductionmentioning
confidence: 99%